ความอยู่ดีมีสุขของวัยรุ่น: การวิเคราะห์อภิมานโมเดลสมการเชิงโครงสร้าง - นัฏฐิกา เจริญตะคุ (จุฬาลงกรณ์มหาวิทยาลัย, 2019)
This study aimed 1) to study the 3 factors of research characteristics including publishing, content and research methodology that affect either effect size of emotional which were emotional intelligence, gratitude, coping style, social support and autonomy support that affected on the well-being of adolescences. 2) to construct and validate causal correlation model of emotional intelligence, gratitude, coping style, social support, and autonomy support effected on well-being of adolescents. Research samples were 67 from 61,696 causal correlation research in well-being of adolescents which were published during 2007-2019. MASEM was applied using R and Mplus. The results of the study were as follows:1. All of research characteristics affected on effect sizes of emotional intelligence, gratitude, coping style, social support, and autonomy support on well-being of adolescents with effect sizes as .23-0.58, .19-0.56, 0.19-0.31, 0.20-0.55 and 0.20-0.47 respectively. Effect sizes of each factor were influenced from research characteristics in different ways.2. Proposed structural equation model of well-being of adolescents consisted of 4 factors: emotional intelligence, social support, coping style, and gratitude that explained the variation of adolescence’s well-being in accounting for 18.3%. The model was fitted with the empirical data (χ2= 2.518, df= 1, p-value= .113, CFI= 1.000, TLI= 1.000, RMSEA= .006). Emotional intelligence had the greatest effect on well-being of adolescences, followed by gratitude, coping style, and social support (.249, .245, .116, and .141 respectively).